2022
DOI: 10.15507/1991-9468.106.026.202201.130-145
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Social Media into Daily Activity of Adolescents and Self-Regulation Characteristics

Abstract: Introduction. Diverse domains of life become more digitalized, social media (social networks, blogs, and information sharing services) have become an intrinsic element of daily life and activities such as education. Positive and negative consequences of social media use were discovered, which increased the awareness of their involvement in adolescents’ and young people’s psychological well-being and socializing. However, the characteristics of self-regulation in the context of increased social media usage rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Based on the research results, it was found that most of the respondents had received information related to self-control abilities, whether from the internet, teachers, or family. Information is something that is very important in increasing one's selfcontrol [21]. Adequate and appropriate information will make it easier for someone to understand something so that one's selfcontrol can increase.…”
mentioning
confidence: 99%
“…Based on the research results, it was found that most of the respondents had received information related to self-control abilities, whether from the internet, teachers, or family. Information is something that is very important in increasing one's selfcontrol [21]. Adequate and appropriate information will make it easier for someone to understand something so that one's selfcontrol can increase.…”
mentioning
confidence: 99%